Georgia Architectural and Historic Properties Survey of 216 Walnut St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 216 Walnut St., Valdosta, Ga., December 1980. 1 story square shaped shiplap sided house with hipped tin roof and exposed rafters. Interior chimney. Shed porch held up by turned spindle posts. Double hung sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: App. 1905-1915. Significant as part of a potential N.R. district which would cover a 4 or 5 block area.
Georgia Architectural and Historic Properties Survey of 216 Walnut St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 78.1 MB (81,927,983 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)